2013
DOI: 10.1387/ijdb.130006cp
|View full text |Cite
|
Sign up to set email alerts
|

Cycling to and from a stem cell niche: the temporal and spatial odyssey of mitotic male germ cells

Christopher J. Payne

Abstract: The development of male germ cells within the prenatal and prepubertal periods in mammals combines multiple biological events that integrate cell cycle regulation, epigenetic reprogramming, and cell migration along temporally and spatially dynamic lines. Germ cells arise from their precursor primordial germ cells in the mid-gestation embryo, forming gonocytes that enter G 0 phase cell cycle arrest within the fetal testis. Cyclin-dependent kinase inhibitors, activated retinoblastoma 1 protein, and increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…Using cell line models and whole-mouse testes, Zhang et al (2013a) reported that long and short transcripts of Kit are expressed in spermatogonia, the long transcript being mainly expressed in the cytoplasm and cell membrane, while the short transcript was found in nuclei as well as the cytoplasm and cell membrane. They also reported that the long transcript of Kit was not expressed in SSCs, in line with other studies (Payne 2013). This group concluded that there are extensive transcriptional and translational changes in KIT expression before and after SSCs differentiation (Zhang et al 2013a).…”
Section: Spermatogonia and Ssc Differentiationsupporting
confidence: 57%
“…Using cell line models and whole-mouse testes, Zhang et al (2013a) reported that long and short transcripts of Kit are expressed in spermatogonia, the long transcript being mainly expressed in the cytoplasm and cell membrane, while the short transcript was found in nuclei as well as the cytoplasm and cell membrane. They also reported that the long transcript of Kit was not expressed in SSCs, in line with other studies (Payne 2013). This group concluded that there are extensive transcriptional and translational changes in KIT expression before and after SSCs differentiation (Zhang et al 2013a).…”
Section: Spermatogonia and Ssc Differentiationsupporting
confidence: 57%
“…All told, we found that at least 33 known “migration genes” are regulated by Rhox10 . This was intriguing given that the migration of ProSG to the periphery of seminiferous tubules accompanies their differentiation into SSCs (Culty, 2009; Payne, 2013). The linkage of these two events, coupled with the finding that Rhox10 regulates batteries of migration genes and promotes SSC generation, led us to test whether Rhox10 has a role in ProSG migration.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Pdgfrb and Dab2ip , have been directly shown to drive ProSG migration in neonatal testes (Basciani et al, 2008; Xu et al, 2015). Of note, Pdgfrb not only promotes ProSG migration but also the accompanying step, resumption of ProSG proliferation (Basciani et al, 2008; Payne, 2013; Thuillier et al, 2010). Given that we obtained evidence that Rhox10 also acts on the same two developmental steps—promoting the differentiation of mitotically inactive ProSG (T1-ProSG) into mitotically active ProSG (T2-ProSG) and driving the migration of T2-ProSG into the SSC niche—it is tempting to speculate that Pdgfrb is a key effector gene downstream of RHOX10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, the predominant model for this system consists of a putative stem cell referred to as an A single (A s ) spermatogonium, which divides to generate either 2 additional A s spermatogonia or interconnected A paired (A pr ) daughter cells that do not complete cytokinesis. 1 4 , Intermediate (In), and Type B differentiating spermatogonia before forming pre-leptotene spermatocytes that initiate entry into meiosis. Despite many years of research on male germline stem cell differentiation, this process has not been fully deciphered at the molecular level.…”
mentioning
confidence: 99%